2015
DOI: 10.1097/phh.0000000000000040
|View full text |Cite
|
Sign up to set email alerts
|

Immunization Information Systems

Abstract: This article reports on a study of laws, regulations, and policies governing Immunization Information Systems (IIS, also known as “immunization registries”) in states and selected urban areas of the United States. The study included a search of relevant statutes, administrative codes and published attorney general opinions/findings, an online questionnaire completed by immunization program managers and/or their staff, and follow-up telephone interviews. The legal/regulatory framework for IIS has changed consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…14 We compared respondents with nonrespondents on all available characteristics using Wilcoxon and chi-square analyses. For relevant questions, where differences existed, responses were reported on the basis of whether or not respondents practiced in a state with an IIS with a mandatory reporting requirement 15 and whether or not respondents were in a large (≥5 providers) or small (<5 providers) practice. Because of the high number of comparisons within these bivariate analyses, we considered statistical significance as <0.01.…”
Section: Methodsmentioning
confidence: 99%
“…14 We compared respondents with nonrespondents on all available characteristics using Wilcoxon and chi-square analyses. For relevant questions, where differences existed, responses were reported on the basis of whether or not respondents practiced in a state with an IIS with a mandatory reporting requirement 15 and whether or not respondents were in a large (≥5 providers) or small (<5 providers) practice. Because of the high number of comparisons within these bivariate analyses, we considered statistical significance as <0.01.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative source of comparison coverage would be immunization information systems, but reporting of influenza vaccination for children is not mandatory in all states. 35 The majority of pediatric deaths with unknown vaccination status had no documentation of influenza vaccination in immunization information systems and were likely unvaccinated; sensitivity analyses treating these deaths as unvaccinated resulted in higher VE estimates. Vaccination coverage in the comparison cohorts was likely intermediate between estimates based on parental report and those based on insurance claims.…”
Section: Discussionmentioning
confidence: 96%
“…A recent survey of 53 IISs demonstrated that 59% mandate that at least one type of provider or entity report immunizations to the IIS, 23% mandate that immunizations for all age groups be reported, and 32% that immunizations for children, adolescents, and younger adults be reported. 20 All but three IISs have several of the functionalities about which the survey inquired, including a forecasting function for routine childhood immunizations to guide providers about needed recommended immunizations, a vaccine inventory function, the ability to generate lists of patients needing vaccinations for reminder/recall, and the ability to create provider site coverage reports. 4,21,22 The majority of GIMs who knew of the existence of an IIS did not know if it had any of these basic functionalities.…”
Section: Discussionmentioning
confidence: 99%